Enzyme inhibition; chymotrypsin - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
‘Efficient’ enzymes, Enzyme inhibition, Competitive inhibition, Non-competitive inhibition, Irreversible inhibition, Diagrams of enzyme mechanisms, Chymotrypsin mechanism
Reviewed at 2022/11/27